Pemanfaatan Teknologi Probio_Fm dalam Penerapan Sistem Integrasi Sapi Kelapa Sawit di Bangka Tengah - Yudi Sapta Pranoto; Fournita Agustina; Rufti Puji Astuti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The integrated cattle and oil palm system is part of an excellent program of the Bangka Tengah Regency to increase the production of plantation and livestock. The benefit of the system is ensuring the availability of the animal feed derived from oil palm plantation waste while the feces of cattle is potential in producing the fertilizer for oil palm. The community service aims to alter the paradigm of the society on the integrated cattle and oil palm system as well as to empower the people to implement the system. Four steps were used as the methods to implement the programs are preparation; socialization; simulation; and monitoring and evaluation. Qualitative descriptive was employed to analyze the data. The program found that 90% of stock farmers agreed that the system was easily doable. The stock farmers were able to use the probio_Fm technology in implementing the system by making the silage made from the oil palm plantation waste. The knowledge of beneficiaries had increased and their behavior in feeding activities had positively altered through the program. It was found that the livestock required a week to adapt to the silage as the fermented materials in the probio-Fm technology. The use of a chopping machine was able to be a choice as it was able to produce the smoother chopped midrib. It concludes that the system is sustainably used to be implemented by Tunas Baru stock farmer.